2017
DOI: 10.1111/sms.12999
|View full text |Cite
|
Sign up to set email alerts
|

Glucose response to exercise in the post‐prandial period is independent of exercise intensity

Abstract: This study investigated the acute glucose response to low-intensity, moderate-intensity, and high-intensity interval exercise compared to no-exercise in healthy insufficiently active males using a four-arm, randomized, crossover design. Ten males (age: 37.3 ± 7.3 years, BMI: 29.3 ± 6.5 kg·m ) completed four 30-minute interventions at weekly intervals comprising low-intensity exercise (LIE) at ~35% V˙O R, moderate-intensity exercise (MIE) at ~50% V˙O R, high-intensity interval exercise (HIIE) at ~80% V˙O R, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…Immediate glucose responses to exercise are variable and likely to be of very short duration; nonetheless, brief improvements in glucose regulation contribute to overall glycaemic control [64]. However, exercise should be participated in frequently to optimise the metabolic responses to mitigate the risk of developing IFG or type 2 diabetes [65]. Interval training appears to be safe; the nature of and frequency of adverse events is not different to continuous aerobic exercise training.…”
Section: Physical Activitymentioning
confidence: 99%
“…Immediate glucose responses to exercise are variable and likely to be of very short duration; nonetheless, brief improvements in glucose regulation contribute to overall glycaemic control [64]. However, exercise should be participated in frequently to optimise the metabolic responses to mitigate the risk of developing IFG or type 2 diabetes [65]. Interval training appears to be safe; the nature of and frequency of adverse events is not different to continuous aerobic exercise training.…”
Section: Physical Activitymentioning
confidence: 99%
“…Interestingly, HIT improves performance with a lower time commitment compared with continuous moderate-intensity training (1.5 vs 4.5 h/week, respectively), making HIT an alluring alternative for the engaged contemporary lifestyle [ 38 ]. In addition, an acute HIT bout effectively lowers blood glucose levels to a similar extent as an isocaloric bout of moderate intensity [ 39 ]. An RCT has shown that 3 months of HIT lowers fasting glucose (by 0.7 mmol/l), reduces HOMA-IR (by 25%) and decreases glycaemic variability (by 5%) in individuals with type 2 diabetes [ 40 ].…”
Section: Effects Of Training Volume and Intensity On Metabolic Adaptamentioning
confidence: 99%
“…There is general agreement among researchers that timely postmeal exercise lowers blood glucose levels in a variety of populations (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). However, postmeal exercise with a high energy expenditure may cause hyperglycemia (25,26) or hypoglycemia (36,37).…”
Section: Postmeal Exercisementioning
confidence: 99%
“…However, postmeal exercise with a high energy expenditure may cause hyperglycemia (25,26) or hypoglycemia (36,37). Studies comparing premeal walks and postmeal walks and focusing on the immediate (,24-hour) glucose response have identified timely postmeal exercise as the better option to deal with meal-related glucose surges in different populations (32)(33)(34)(35)(52)(53)(54)60,61).…”
Section: Postmeal Exercisementioning
confidence: 99%
See 1 more Smart Citation